Biocompatibility of a New Antibacterial Compound and its Effect on the Mechanical Properties of Flowable Dental Composites (Animal Study) - Mehdi Abaszadeh; Meisam Mohammadi; Iman Mohammadzadeh (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Recently, new compound of 3, 5-dimethyl-1-thiocarboxamide pyrazole has been composed with excellent antibacterial property. Biocompatibility and its effects on mechanical properties of dental composites should be considered before clinical use. Purpose: The purpose of this study was to evaluate the biocompatibility of 3, 5-dimethyl-1-thiocarboxamide pyrazole as a new antibacterial compound and its effect on the mechanical properties of dental composites. Materials and Method: In this experimental study, a new antibacterial compound was synthesis by reaction between Thiosemicarbazide and 2, 4-Pentandione and tested on thirty male albino Wistar rats weighting 200-250gr. Rats were randomly divided into 3 groups of 10, each rat received 3 implants of 3,5-dimethyl-1-thiocarboxamide pyrazole, penicillin v and empty polyethylene tube. A pathologist, who was unaware of types of tested materials and timing, performed the examination of specimens. The depth of cure and flexural strength of resin composite was measured using Iso4049 standard technique. Compressive strength was determined according to Iso9917 standard. Results: This compound was biocompatible and there was no significant difference in flexural strength and compressive strength of the composites containing 1% of this compound with the control group (p> 0.05). Conclusion: The 3, 5-dimethyl-1-thiocarboxamide pyrazole with a concentration of 1% in flowable composites can be very effective in preventing secondary caries.